Geographical distribution of centenarians in Colombia: an analysis of three databases (2017)
Introduction: Individuals aged one hundred years or more are of interest for the study of the aging process, which has been scarcely addressed in Colombia.Objective: To estimate the number and geographical distribution of centenarians in Colombia.Materials and methods: Three sources of information were reviewed: the 2005 Census, the death certificates issued from 2010 to 2013, and the Individual Registries of Health Services Provision (RIPS in Spanish) of 2014.Results: The census recorded data of 3 165 centenarians (1 972 women, 62.3%), finding the highest rates in La Guajira (2.23 x 10 000), Chocó (1.90) and Sucre (1.61). In the four-year period analyzed, 3 611 people died, with the highest proportions (for every 1 000 deaths) found in Chocó (10.4), La Guajira (9.4) and Sucre (6.5). RIPS identified 3 390 centenarians, with a higher frequency in Sucre (2.17 x 10000), Chocó (1.29) and Córdoba (1.11).Conclusions: Although the results are consistent with the number and geographical distribution of centenarians, some errors may be found in the date of birth stated in the records, which is the basis for estimating age in the three sources. Other factors potentially involved in the results may be physical activity, family and community support, low stress and healthy diet in these regions.